Functional response of subordinate species to intraspecific trait variability within dominant species. (19th August 2019) - Khalil, Mohammed I.; Gibson, David J.; Baer, Sara G.
Abstract: Dominant species can act as a biotic filter in structuring plant communities by constraining the establishment and survival of subordinate species. The effect of intraspecific trait variability of dominant species on the functional response of subordinate species, however, is not well understood. We quantified intraspecific variation in four functional traits of 26 subordinate species in an experimental grassland established with two population sources (i.e. cultivars and local ecotypes) of three dominant grasses ( Sorghastrum nutans, Andropogon gerardii and Schizachyrium scoparium ) and three pools of subordinate species (each from one origin) within each of the dominant grass source treatments. Twenty of the 26 subordinate species exhibited intraspecific trait variability for one trait or more in response to dominant species population source, and variation among population sources of the dominant species was non‐random. Dominant grass population source affected intraspecific variability in functional traits of multiple subordinate species. Cultivar sources of the dominant grasses and some of the subordinate species that established with them had higher and generally more variable functional leaf area and leaf nitrogen content compared to local ecotypes of the dominant grasses and the subordinate species that established with them. Local ecotype sources of the dominant grasses increased leaf area based functional diversity of subordinate species. Synthesis. This study provides evidence that intraspecific trait variability in dominant species acts as a biotic filter to constrain niche availability and dimensionality affecting trait variation of subordinate species during community assembly. Abstract : In an experimental grassland restoration, we show that intraspecific functional trait variability in three dominant species acts as an inner biotic filter to affect functional diversity, and constrain niche availability and dimensionality affecting trait variation of 20 of 26 subordinate species. Intraspecific trait variability contributes to community assembly and has implications for predicting restoration success. Kurdish Abstract: ردارکردنی جێگیربوون و مانەوەی جۆرە لاوەکییەکان. هەروەها تێگەیشتنێکی تەواو نییە لە سەر کاریگەری هەبەوونی جیاوازی لە جۆرە زاڵەکان لەسەر کاردانەوەی فەرمانی جۆرە لاوەکییەکان. هەستاین بەهەژمارکردنی کاریگەری جیاوازی نێو جۆرەکان لە سەر چوار خەسلەتی فەرمانی ٢٦ جۆری بەزیو کە لە تاقیکردەوەیەکی گژوگیادا جێگیر کرابوون لە گەڵ دوو گروپی زاڵ بەڵام لە ڕووی ژینگەییەوە جیاواز)گروپی جێنراوەدەستکاریکراوەکان و ناوچەییەکان یان ناوخۆییەکان(بۆ جورە زاڵەکان کە بریتی بوون لە سێ جۆری گیایی زاڵ (Andropogon gerardii, Sorghastrum nutans, Schizachyrium scoparium) هەروەها سێ جۆری لاوەکی جیاواز دابەشکرابوونە سەر جۆرە زاڵەکان. لە ئەنجامی کاریگەری جۆرە زاڵەکان لە سەر جۆرە لاوەکییەکان، لە کۆی ٢٦ جۆری لاوەکی ٢٠ جۆریان جیاواز بوون لە خەسڵەتە ناوخۆییەکان. جیاوازییەکان لە یەک خەسڵەت یان زیاتر بوون، هەروەها جیاوازییەکان لە نێو جۆرە زاڵەکان هەڕەمەکی نەبوون. خەسڵەتی جۆرە چێنراوەدەسکاری کراوە زاڵەکان و ئەو جۆرەلاوکییەیانەی کە لە گەڵیاندا ڕووا بوون و گەشەیان کردبوو جیاوازتربوون لە خەسڵەتی جۆرە ناوچەییە زاڵەکان و ئەو جۆرە لاوەکییانەی کە لە گەڵیاندا ڕووابوون و گەشەیان کردبوو. ڕووبەری گەڵا و بڕی نایترۆجین لە گەڵای جۆرە چینراوەدەسکاریکراوە زاڵەکان و ئەو جۆرە لاوەکیانەی کە لەگەڵیاندا ڕووابوون گەشەیانکردبوو زیادتر بوون لە ئەوانی تر. لە ئەنجامدا، بەڵگەکانی ئەم یوێژینەوە ئوە دەسەڵمێنێت کە جیاوازی لە خەسڵەتە فەرمانییەکانی جۆرە زاڵەکان وەک پاڵاوتنێکی زیندوو کاریگەری هەیە لە سەر جۆرە لەوەکییەکان لەکاتی دروستبوونی کۆمەڵەی ڕووەکی. کەمی جیاوازی لە خسڵەتەکانی نێوان جۆرەزاڵەکان بووەتە هۆکاری بوونی جیاوازی لە جۆرە لاوکییەکاندا، ئەمەش ئەوە دەردەخات کە کەمی جیاوازی خەسڵەتەکانی جۆرە زاڵەکان کاردەکاتە سەر سنووردارکردنی شوێنی گەشەکردن و مانەوەی ڕووەکەکان.